2004
DOI: 10.1002/mop.20495
|View full text |Cite
|
Sign up to set email alerts
|

A wideband printed dipole antenna with optimized tapered feeding balun for ISM and FWA bands

Abstract: GHz. The poor match, excess losses, and frequency shift of ϳ0.4 GHz can be attributed to losses due to coaxial connectors, conductor and dielectric losses, impedance mismatch, and fabrication errors, respectively, which were not considered in the simulation. No attempt for circuit tuning and iterations in the simulation were made in the proof-of-concept phase. CONCLUSIONA novel compact BPF using Chebyshev multisection transformer has been presented. The filter has dimensions similar to those of the hairpin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A single-element antenna without any bandwidth enhancements has been previously reported by the authors in [9], in which 58% impedance bandwidth was demonstrated by simply matching the feeding network (that is, a microstrip tapered balun) to the radiating element. In this paper, we present an enhancement to this antenna, using only an additional coplanar parasitic element, and optimizing the main geometry parameters for over-an-octave bandwidth.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…A single-element antenna without any bandwidth enhancements has been previously reported by the authors in [9], in which 58% impedance bandwidth was demonstrated by simply matching the feeding network (that is, a microstrip tapered balun) to the radiating element. In this paper, we present an enhancement to this antenna, using only an additional coplanar parasitic element, and optimizing the main geometry parameters for over-an-octave bandwidth.…”
Section: Introductionmentioning
confidence: 90%
“…However, we proposed in [9] that adequate performance is achieved even for greater opening angles a (in this case, a ϭ 4Њ), yielding a taper length of approximately 14.75 mm, which is much smaller than a wavelength. Hence minimal size is maintained, which is important for the compactness of the radiator.…”
Section: Antenna Design and Simulationmentioning
confidence: 98%
See 2 more Smart Citations
“…To comply with this requirement, compact and high-performance broadband/multiband planar antennas with good radiation characteristics are needed. Recently, various types of printed dipole antennas (PDAs) have been studied, as they provide easy fabrication, a simple structure, and easy integration of solid-state devices [1][2][3]. In particular, the double-sided printed dipole-antenna is one of the techniques concerning the enhancement of the impedance bandwidth, and the antenna-size reduction in case of multiband operation [4 -6].…”
Section: Introductionmentioning
confidence: 99%